Value Creation and Efficiency: Incompatible or Inseparable?. (May 2018) - Davidow, Moshe
Abstract: The efficiency/value creation (effectiveness) debate has been mostly one sided through the years in favor of efficiency. However, a new way of looking at things has started to even out the balance. In this article, we will discuss both sides of the debate, state the underlying problem at the base of the debate, and give examples of how this debate actually destroys value. In most cases, this failure is not really a failure, but was designed into the system by misguided managerial choices. We then present our solution based on thinking holistically about productivity and efficiency in a world of co-creation, and discuss ways for managers to implement it in their organizations. This implementation is based on current examples from the literature, as well as a discussion as to why these ways are so effective. In a sense, in a world of co-creation, efficiency becomes less important, as the customer is willing to pay more money for a higher value product, thus covering the cost of a slightly less efficient process.